Report of a False Positive Rapid HIV Test Due to Hepatitis A in a U.S. Army Soldier - Contrina, A Huffman; Rachel, N. Barts; Cristóbal, S. Berry-Cabán; Y., Sammy Choi (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
A 25 year old, single, active duty soldier presented to a clinic in Afghanistan complaining of malaise, fatigue, acholic stools, and mild jaundice over a 5- to 7-day period. He had significantly elevated liver transaminase levels approaching 5000 U/L and a positive rapid human immunodeficiency (HIV) 1 antibody test. Ultimately, the patient was found to have a false positive rapid HIV-1 antibody test due to acute hepatitis A virus infection. This case report describes his evaluation and outcome, in addition to exploring possible causes of false positive HIV screening.
Keywords: False positive HIV test; Rapid HIV test; Hepatitis A; HIV antibody; Confirmatory HIV test